2015
DOI: 10.1063/1.4926880
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer upon collision of selectively excited CO2 molecules: State-to-state cross sections and probabilities for modeling of atmospheres and gaseous flows

Abstract: Carbon dioxide molecules can store and release tens of kcal/mol upon collisions, and such an energy transfer strongly influences the energy disposal and the chemical processes in gases under the extreme conditions typical of plasmas and hypersonic flows. Moreover, the energy transfer involving CO2 characterizes the global dynamics of the Earth-atmosphere system and the energy balance of other planetary atmospheres. Contemporary developments in kinetic modeling of gaseous mixtures are connected to progress in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…Another problem arises with the new PVM dissociation constants from Equation in particular due to the dependence of heavy particle dissociation rate on the vibrational energy of CO 2 . The phenomenological approach, that considers the vibrational energy entering the Arrhenius law (see Equation ) multiplied by a factor 0.8, should be clarified especially if the non‐equilibrium vibrational distributions reported in this paper, as well as in ref., will resist to future improvements of V‐V and V‐T rates …”
Section: Resultsmentioning
confidence: 99%
“…Another problem arises with the new PVM dissociation constants from Equation in particular due to the dependence of heavy particle dissociation rate on the vibrational energy of CO 2 . The phenomenological approach, that considers the vibrational energy entering the Arrhenius law (see Equation ) multiplied by a factor 0.8, should be clarified especially if the non‐equilibrium vibrational distributions reported in this paper, as well as in ref., will resist to future improvements of V‐V and V‐T rates …”
Section: Resultsmentioning
confidence: 99%
“…Finally, the molecules are randomly oriented, with the initial intermolecular distance set large enough to make the interaction between them negligible. The vibrational state of the linear CO 2 molecule requires four quantum numbers; however, the one corresponding to the vibrational angular momentum can be disregarded, since bending states with significant rotational energy are unlikely (i. e. the rotational energy with respect the molecular axis is in general very low [54]). The above scheme is suited for VV and VT exchange processes, since cross sections and probabilities obtained from the trajectories are specific for vibrational states, but thermally averaged over rotations (at the given rotational temperature).…”
Section: The Quasiclassical Trajectory Methodsmentioning
confidence: 99%
“…Actually, more refined rate coefficient calculations can be provided by using the forced harmonic oscillator (FHO) theory [49][50][51][52][53] or by using an appropriate potential energy surface (PES) and a quasi-classical trajectory (QCT) dynamic method. The latter approach has been already used for the derivation of some VV and VT transition rates but could be extended also to other transitions [54][55][56], while the FHO theory was used to calculate an extensive matrix of VV and VT transitions for CO 2 very recently [52].…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational state of the linear CO 2 molecule is defined by three quantum numbers (see below), since one of them, corresponding to the vibrational angular momentum, is disregarded. This assumption has been discussed and motivated in a series of previous works on CO 2 , [25][26][27] where it was observed that the bending states with high rotational energy are unlikely and the energy associated with the vibrational angular momentum is negligible (see, e.g., Ref. [26], where the time evolution of the radial and angular energy associated with the bending has been considered in typical cases).…”
Section: Full Paper Wwwc-chemorgmentioning
confidence: 91%